A mathematical model for swimming mechanics - Seireg, A. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
This paper presents a simplified mathematical model for analysis of swimming mechanics. The effect of the motions of upper and lower extremities on the swimming speed is discussed. The model is based on results from experimental data obtained by the authors from simulated tests. The model illustrates the influence of the main parameters affecting swimming.